A rapamycin-sensitive signaling pathway contributes to long-term synaptic plasticity in the hippocampus - Tang, Shao Jun (The National Academy of Sciences, 2002)
Many forms of long-lasting behavioral and synaptic plasticity require the synthesis of new proteins. For example, long-term potentiation (LTP) that endures for more than an hour requires both transcription and translation. The signal-transduction mechanisms that couple synaptic events to protein translational machinery during long-lasting synaptic plasticity, however, are not well understood. One signaling pathway that is stimulated by growth factors and results in the translation of specific mRNAs includes the rapamycin-sensitive kinase mammalian target of rapamycin (mTOR, also known as FRAP and RAFT-1). Several components of this translational signaling pathway, including mTOR, eukaryotic initiation factor-4E-binding proteins 1 and 2, and eukaryotic initiation factor-4E, are present in the rat hippocampus as shown by Western blot analysis, and these proteins are detected in the cell bodies and dendrites in the hippocampal slices by immunostaining studies. In cultured hippocampal neurons, these proteins are present in dendrites and are often found near the presynaptic protein, synapsin I. At synaptic sites, their distribution completely overlaps with a postsynaptic protein, PSD-95. These observations suggest the postsynaptic localization of these proteins. Disruption of mTOR signaling by rapamycin results in a reduction of late-phase LTP expression induced by high-frequency stimulation; the early phase of LTP is unaffected. Rapamycin also blocks the synaptic potentiation induced by brain-derived neurotrophic factor in hippocampal slices. These results demonstrate an essential role for rapamycin-sensitive signaling in the expression of two forms of synaptic plasticity that require new protein synthesis. The localization of this translational signaling pathway at postsynaptic sites may provide a mechanism that controls local protein synthesis at potentiated synapses.